Agribusiness Development of Flavor Rice “Mandoti” in Enrekang Districts - Khayam, Omar Khayam; Irmayani, Dr.Irmayani; Amaluddin, Amaluddin (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Enrekang Regency is one of the areas in South Sulawesi with a topography of producing vegetable commodities, but apart from that this area also produces superior commodities that are only produced in Salukanan Village, Baraka District, namely local rice flavored rice known as "Pulu Mandoti". This study aims to analyze external factors (strengths and weaknesses) and internal factors (opportunities and threats) to formulate a development strategy for agribusiness development of "Pulu Mandoti" flavored rice. This research was carried out in Enrekang Regency, by determining several respondents who involved the head of the agriculture department, epala Bappeda, the head of Gapoktan. The analysis used is process hierarchical analysis, which shows that the strategy to develop flavored rice known as "Pulu Mandoti" starts from technical aspects, policy aspects and economic aspects.